Revisiting The Finance-Innovation Nexus: Evidence from Asia - Wen, Jun; Chima, Hernandez Maria Fernanda; Salim, Agus (JAMPE (Journal of Asset Management and Public Economy), 2025)
Since a few studies have analysed the long-run impact of monetary policy, this study aims to contribute to this gap by revisiting the Schumpeterian finance-innovation nexus and examining the influence of monetary policy, as well as the mediating function of bank lending, on technological innovation across Asian economies. This study employs a fixed-effect model (FEM) to analyse a cross-country dataset of Asian economies from 2002 to 2023. The finding reveals the direct and indirect correlation between monetary policy and innovation, as determined through mediating regression analysis. Furthermore, our study offers empirical evidence supporting a correlation between financial development and national innovation. This finding holds across several primary, robustness, and endogeneity analyses. Furthermore, this study also found that the direct and indirect effects of monetary policy on national innovation are more pronounced in upper-middle- and high-income countries. This study confirms that enhanced bank lending, facilitated by appropriate monetary policy, has a favourable and statistically significant impact on national innovation.